Circuit techniques for dynamic variation tolerance - Bowman, Keith; Tschanz, James; Wilkerson, Chris; Lu, Shih-Lien; Karnik, Tanay; De, Vivek; Borkar, Shekhar (2009 46th ACM/IEEE Design Automation Conference, 2009)
Three circuit techniques for dynamic variation tolerance are presented: (i) Sensors with adaptive voltage and frequency circuits, (ii) Tunable replica circuits for timing-error prediction with error recovery, and (iii) Embedded error-detection sequential circuits with error recovery. These circuits mitigate the clock frequency guardbands for dynamic variations, thus improving microprocessor performance and energy-efficiency. These circuits are described with a focus on the different trade-offs in guardband reduction and design overhead. Opportunities for CAD to further enhance microprocessor performance and energy efficiency are offered.